The clinical spectrum of laryngeal dystonia includes dystonic cough: Observations of a large series. Issue 6 (18th April 2014) - Payne, Susannah; Tisch, Stephen; Cole, Ian; Brake, Helen; Rough, Judy; Darveniza, Paul
ABSTRACT Laryngeal dystonia is a movement disorder of the muscles within the larynx, which most commonly manifests as spasmodic dysphonia (SD). Rarer reported manifestations include dystonic respiratory stridor and dyscoordinate breathing. Laryngeal dystonia has been treated successfully with botulinum neurotoxin (BTX) injections since 1984. We reviewed prospectively collected data in a consecutive series of 193 patients with laryngeal dystonia who were seen at St. Vincent's Hospital between 1991 and 2011. Patient data were analyzed in Excel, R, and Prism. Laryngeal dystonia manifested as SD (92.7%), stridor (11.9%), dystonic cough (6.2%), dyscoordinate breathing (4.1%), paroxysmal hiccups (1.6%), and paroxysmal sneezing (1.6%). There were more women (68.4%) than men (31.6%), and the average age at onset was 47 years. A positive family history of dystonia was present in 16.1% of patients. A higher incidence of extra‐laryngeal dystonia (ie, torticollis and blepharospasm) and concurrent manifestations of laryngeal dystonia were present in patients with dystonic cough, dyscoordinate breathing, paroxysmal sneezing, and hiccups than in other patients (P = 0.003 and P < 0.0001, respectively). The average starting dose of BTX decreased from 2.3 to 0.5 units between 1991 and 2011. The median treatment rating was excellent across all subgroups. Patients with adductor SD, stridor, extra‐laryngeal dystonia and male patients had relatively better treatment outcomes. Technical failures were rare (1.1%). Dysphonia secondary to vocal cord paresis followed 38.7% of treatments. Laryngeal dystonia manifests predominantly as SD, but other manifestations include stridor, dyscoordinate breathing, paroxysmal cough, hiccups, and sneezing. BTX injections are very effective across all subgroups. Severe adverse events are rare. © 2014 International Parkinson and Movement Disorder Society